2022
DOI: 10.1021/acs.jnatprod.2c00020
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from Sauropus spatulifolius Leaves with Antimicrobial Activities

Abstract: As a plant used in both food and medicine, Sauropus spatulifolius is consumed widely as a natural herbal tea, food source, and Chinese medicine. Inspired by its extensive applications, we conducted a systematic phytochemical study of the leaves of S. spatulifolius. Thirteen new diterpenoids, sauspatulifols A–M (1–13), including four ent-cleistanthane-type diterpenoids (1–4), eight 15,16-di-nor-ent-cleistanthane-type diterpenoids (5–12), and one 17-nor-ent-pimarane-type diterpenoid (13) as well as one known dit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Diterpenes are produced by the mevalonate biosynthetic pathway leading to the condensation reaction of isopentenyl pyrophosphate and farnesyl pyrophosphate (Eksi et al, 2020). According to Wu, Cui et al (2022) and Wu, Yang et al (2022), two diterpenoids with good antimicrobial activity were identified from the leaves of Sauropus spatulifolius, a plant used for food and medicine. Among these diterpenoids, sauspatulifol E (96) and cleistanthol (97) exhibited good antimicrobial activity against S. aureus, S. epidermidis, and M. luteus with the same MIC value of 32 and 12 μg/mL, respectively (Wu, Cui, et al, 2022;Wu, Yang et al 2022).…”
Section: Diterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diterpenes are produced by the mevalonate biosynthetic pathway leading to the condensation reaction of isopentenyl pyrophosphate and farnesyl pyrophosphate (Eksi et al, 2020). According to Wu, Cui et al (2022) and Wu, Yang et al (2022), two diterpenoids with good antimicrobial activity were identified from the leaves of Sauropus spatulifolius, a plant used for food and medicine. Among these diterpenoids, sauspatulifol E (96) and cleistanthol (97) exhibited good antimicrobial activity against S. aureus, S. epidermidis, and M. luteus with the same MIC value of 32 and 12 μg/mL, respectively (Wu, Cui, et al, 2022;Wu, Yang et al 2022).…”
Section: Diterpenoidsmentioning
confidence: 99%
“…According to Wu, Cui et al (2022) and Wu, Yang et al (2022), two diterpenoids with good antimicrobial activity were identified from the leaves of Sauropus spatulifolius, a plant used for food and medicine. Among these diterpenoids, sauspatulifol E (96) and cleistanthol (97) exhibited good antimicrobial activity against S. aureus, S. epidermidis, and M. luteus with the same MIC value of 32 and 12 μg/mL, respectively (Wu, Cui, et al, 2022;Wu, Yang et al 2022). Kaempferia roscoeana is a commonly used spice in Thai cuisine.…”
Section: Diterpenoidsmentioning
confidence: 99%
“…Using this method to break down complex molecules can often yield promising results, as shown in this paper by J. M. Smith et al introducing such method of retrosynthesis [3] . Herbal tea and dried leaves made from the cleistanthol containing plant Sauropus spatulifolius Beille had been considered a effective treatment to upper respiration pathway inflammation in East and Southeast Asian herbal medicines [4] , and research had also shown that the molecule of interest possesses potential antimicrobial, antivirus, and anticancer values [1,5] , indicating potential commercial values of the synthesis of this molecule. This paper examines a possible retrosynthetic mechanism of the molecule's decomposition, and a synthetic pathway inspired by the retrosynthetic mechanism.…”
Section: Fig 1 Leaves Of Sauropus Spatulifolius Beillementioning
confidence: 99%
“…Cleistanthol, a chemical extracted from Sauropus spatulifolius, a culinary ingredient and herbal medicine [1] , is the center of investigation of this paper. In this paper, a possible synthetic route for the complex polycyclic compound using retrosynthetic methods is being explored (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our continuing efforts to explore structurally interesting and biologically significant secondary metabolites from Chinese medicinal plants, the ethanolic extract of the twigs of B. ramiflora was phytochemically investigated, which resulted in the isolation of four highly oxygenated and rearranged trinorditerpenoids, baccaramiones A–D ( 1–4 ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%